Effects of empagliflozin on the expression of kisspeptin gene and reproductive system function in streptozotocin-induced diabetic male rats - Dana, Parisa; Hayati Roodbari, Nasim; Yaghmaei, Parichehreh; Hajebrahimi, Zahra (Frontiers in Endocrinology, 2022)
One of the main health concerns of diabetes is testicular dysfunction and impairment of reproductive function and sperm quality which can cause male infertility. kisspeptin is a hypothalamic neuropeptide hormone that is involved in the regulation of energy metabolism, gonadotrophin-releasing hormone (GnRH), and reproductive function. In the present study, the therapeutic effects of empagliflozin (sodium-glucose co-transporter 2 inhibitors) on kisspeptin expression along with reproductive function were investigated in diabetic male Wistar rats. Diabetes was induced by a single dose injection of 60 mg/kg streptozotocin. Empagliflozin in doses of 10 and 25 mg/kg body weight was used for 8 weeks. Serum samples, testis, epididymis, and pancreas tissues were collected at the end of the experiments. Lipid profiles, oxidative stress markers, blood hormones, expression of kisspeptin along with pathological alterations of the testis were assayed using real-time PCR, biochemical, and histological technics. Data have shown that empagliflozin improved hyperglycemia, reproductive impairment, oxidative stress condition, and histopathological alterations of pancreatic and testis tissues in diabetic animals. It improved the serum levels of sex hormones, insulin, leptin, and the expression of kisspeptin in the testes tissues. Spermatogenesis is also improved in treated animals. Data indicated that the administration of empagliflozin can ameliorate symptoms of diabetes. It probably has promising antidiabetic potential and may improve the male infertility of diabetic subjects. To our knowledge, this is the first experimental evidence for the potential impact of empagliflozin on kisspeptin expression in diabetic male rats.